2020
DOI: 10.1515/nanoph-2020-0184
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating photonic computing by bandwidth enhancement of a time-delay reservoir

Abstract: AbstractSemiconductor lasers (SLs) that are subject to delayed optical feedback and external optical injection have been demonstrated to perform information processing using the photonic reservoir computing paradigm. Optical injection or optical feedback can under some conditions induce bandwidth-enhanced operation, expanding their modulation response up to several tens of GHz. However, these conditions may not always result in the best performance for computational tasks, sinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 40 publications
(52 reference statements)
0
8
0
Order By: Relevance
“…Figure 4(b) illustrates a photonic RC implementation based on semiconductor lasers that have been used e.g. to decode coherent optical communication signals at high speeds [32].…”
Section: Delay-based Reservoir Computingmentioning
confidence: 99%
“…Figure 4(b) illustrates a photonic RC implementation based on semiconductor lasers that have been used e.g. to decode coherent optical communication signals at high speeds [32].…”
Section: Delay-based Reservoir Computingmentioning
confidence: 99%
“…Semiconductor lasers react highly nonlinearly to optical injection, and previously we showed that this nonlinear response can be harvested to implement the nonlinear nodes of an ANN [26,27]. The feasibility of this concept was shown numerically for 33 GHz [28]. However, here each neuron is physically implemented in parallel via the LA-VCSEL's complex and high-dimensional multimode field.…”
Section: A Photonic Ann In a Complex And Continuous Nonlinear Mediamentioning
confidence: 99%
“…This generic chip can perform arbitrary Boolean logic operations with memory as well as 5-bit header recognition up to 12.5 Gbit s -1 , without power consumption in the reservoir and it can also perform spoken digit recognition. Delay-based reservoirs have been implemented using two different approaches: optoelectronic reservoirs that use laser sources, optical fibres [93] and Mach-Zehnder modulators, and all-optical reservoirs that are based on semiconductor lasers, semiconductor optical amplifiers or passive optical cavities [89]. An example of a delay-based reservoir is described by Dejonckheere et al [94] and it is based on a fully passive nonlinearity, namely the saturable absorption of a semiconductor mirror placed in a ring-like optical cavity.…”
Section: Photonic Reservoir Computingmentioning
confidence: 99%